New Jersey 4-H Marine Science Project. Leaders Guide - Jesuncosky, Betty Jean, Comp.; Rutgers, The State Univ., New Brunswick, NJ. Cook Coll. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
This guide contains a collection of activities which are designed to provide opportunities for 4-H volunteers and youth in New Jersey to get involved in learning about the marine environment. The guide is divided into five sections which deal with habitats, organisms, career exploration, community involvement, and additional marine activities. Each of the sections is comprised of individual lessons, with the intention of including the necessary information for volunteers to provide marine education for 4-H youth. Each lesson is further broken down into seven categories: (1) an introduction; (2) the goals of the lesson; (3) background information; (4) preparation reminders; (5) questions for discussion; (6) additional resources and ideas; and (7) references. The appendices contain reproducible worksheets for use with various lessons and activities, a field trip planning guide, project requirement guidelines, record keeping information, and lists of additional resources. (TW)
Availability: New Jersey Sea Grant, Bldg. 22-Sandy Hook, Ft. Hancock, NJ 07732 (free while supply lasts).
Sponsoring Agency: National Oceanic and Atmospheric Administration (DOC), Rockville, MD. National Sea Grant Program.
Contract Number: NA-85AA-D-SG084.
ERIC Note: Drawings may not reproduce well.
Practitioners.
Community.
Keywords: Art Activities; Ecology; Elementary Education; Elementary School Science; Environmental Education; Experiential Learning; Marine Biology; Marine Education; Science Activities; Science Education; Science Instruction; Social Studies; Youth Clubs; Youth Leaders; New Jersey -- 4 H Programs; Guides, Classroom -- Teacher